2018
DOI: 10.1002/ams2.384
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative educational intervention on procedural sedation and analgesia across the Pacific

Abstract: Aim Worldwide, health‐care providers carry out procedural sedation and analgesia (PSA) in the emergency department. However, training opportunities are limited in many Asian countries, including Japan. We formed an educational group consisting of board‐certified emergency physicians in the USA and Japanese physicians and developed a PSA training module. The aims of our study were to demonstrate the effectiveness of training and to describe PSA practice in Japan. Methods We undertook a pretest of PSA knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“… 19 Similar to propofol for PSA, routine supplemental oxygen may reduce the incidence of hypoxia for the elderly patients receiving thiopental. Notably, capnography is not routinely used in Japanese EDs, 20 thus transient apnea may be overlooked. The incidence of hypoxia could be explained by overlooked apnea; thus, routine use of capnography might need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Similar to propofol for PSA, routine supplemental oxygen may reduce the incidence of hypoxia for the elderly patients receiving thiopental. Notably, capnography is not routinely used in Japanese EDs, 20 thus transient apnea may be overlooked. The incidence of hypoxia could be explained by overlooked apnea; thus, routine use of capnography might need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the type of monitoring and timing of measurements depended on the physician who performed PSA. Japanese EDs do not routinely use capnography, 20 thus transient apnea may be overlooked. Likewise, the incidence of hypotension in our study was low but may be overlooked due to long noninvasive blood pressure measurement intervals.…”
Section: Discussionmentioning
confidence: 99%
“…The course evaluation results showed that health care professionals who participated in the training had a somewhat limited baseline knowledge of pharmacology, elderly patients, timing of AEs, and fasting time on PSA, and that the knowledge was significantly improved after the training. 11 In the sections which follow, we describe concrete procedures for safe PSA in the ED. These procedures include, an evaluation of the patient by an EP, who will also plan for sedative levels and medications.…”
Section: Introductionmentioning
confidence: 99%
“…Second, indications for PSA in the ED are different (Table 1). 2,4,5 Third, emergency physician (EP) training opportunities for PSA in Japan are somewhat limited 11 . The Japanese Procedural Sedation and Analgesia Registry (JPSTAR), a multicenter prospective observational study, showed slightly higher incidence of adverse events (AEs) during PSA in participating EDs in Japan than previous studies in other countries 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation